Impact of Radio Program Civic Voice on Rehabilitation of Free Bonded Labourers in Bardia District - B C, Dilli Bahadur (Academia Research Journal, 2023)
This study focuses on the effect of the radio program Civil Voice on the restoration of free bonded labourers in Bardia district. The study is based on the analysis of the questionnaire survey. The survey covers only the free bonded labourers. Since the program is only focused on the sensitive issue of restoration of free bonded labourers, it is in the interest of this class that has spent a life of slavery and society to focus on the interests of this class. In this way, since the radio program works on the side of slavery, it is natural that the study is attractive. No one has studied this poison before. Therefore, the study focuses on the social responsibility of communication. It was found that the Civil Voice program mainly takes the policy system to free bonded labourer and in the absence of rehabilitation, the problems of free bonded labourers to the implementing agencies. It was found that this program contributed to policy information, government efforts and free bonded labourers to be organized, empowered and aware of their rights.